2015
DOI: 10.1021/acs.nanolett.5b02256
|View full text |Cite
|
Sign up to set email alerts
|

Multivalency at Interfaces: Supramolecular Carbohydrate-Functionalized Graphene Derivatives for Bacterial Capture, Release, and Disinfection

Abstract: A supramolecular carbohydrate-functionalized two-dimensional (2D) surface was designed and synthesized by decorating thermally reduced graphene sheets with multivalent sugar ligands. The formation of host-guest inclusions on the carbon surface provides a versatile strategy, not only to increase the intrinsic water solubility of graphene-based materials, but more importantly to let the desired biofunctional binding groups bind to the surface. Combining the vital recognition role of carbohydrates and the unique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
101
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 112 publications
0
101
0
1
Order By: Relevance
“…[11] One of the inherent problems with phototherapy is the nonspecific cell interactions, as the functioning of heat and ROS does not make a distinction between normal and bacterial cells. [27][28][29] Numerous strains of bacteria express carbohydrate-binding proteins, termed lectins, on their surfaces to mediate critical physiological and pathological activities, for example, adhesion to host cells, biofilm formation, and infection. [23] Current targeting strategies involve the use of antibodies, [24] aptamers, [25] or small molecules such as vancomycin.…”
Section: Doi: 101002/adtp201900052mentioning
confidence: 99%
See 1 more Smart Citation
“…[11] One of the inherent problems with phototherapy is the nonspecific cell interactions, as the functioning of heat and ROS does not make a distinction between normal and bacterial cells. [27][28][29] Numerous strains of bacteria express carbohydrate-binding proteins, termed lectins, on their surfaces to mediate critical physiological and pathological activities, for example, adhesion to host cells, biofilm formation, and infection. [23] Current targeting strategies involve the use of antibodies, [24] aptamers, [25] or small molecules such as vancomycin.…”
Section: Doi: 101002/adtp201900052mentioning
confidence: 99%
“…[27][28][29] Numerous strains of bacteria express carbohydrate-binding proteins, termed lectins, on their surfaces to mediate critical physiological and pathological activities, for example, adhesion to host cells, biofilm formation, and infection. [27][28][29] Here, we use galactosylated Cu 2−x S NCs to target the galactose-specific lectin LecA on the surface of Pseudomonas aeruginosa and eradicate the bacteria via simultaneous PTT and PDT in the NIR II window. Schematic illustration of the surface modification process for the Cu 2−x S NCs and the molecular structure of the tri-thiogalactoside cluster Gal 3 -COOH.…”
Section: Doi: 101002/adtp201900052mentioning
confidence: 99%
“…While this paper was under review, an E. coli capture device built on graphene sheets was reported [80]. The device self-assembles treating adamantyl-functionalized graphene with heptamannosylated β-cyclodextrin (ManCD) and it captures E. coli wrapping it up in the graphene sheet in a reversible fashion.…”
Section: Figurementioning
confidence: 99%
“…Subsequent IR-laser irradiation results in killing of the bacteria and yields these types of materials feasible for disinfection applications. 29 Tran et al reported on the development of a one-step recyclable method to synthesize a supramolecular polysaccharide composite material comprising cellulose, chitosan, and crown ether (B15C5). The composite material demonstrated supramolecular properties, mechanical properties in the range of cellulose mechanical properties and adsorption capability of heavy metal ions and organic pollutants.…”
Section: Supramolecular Biomaterials Inspired By Carbohydratesmentioning
confidence: 99%